A Predominant Physical Component Profile of Persipura Junior Football Athletes - Daniel Womsiwor; N Adiputra; I Made Bakta; Ambrosius Purba; I Made Jawi; I Ketut Suyasa; Nita Fitria (Universitas Pendidikan Indonesia, 2020)
This study was aimed at determining the description of predominant physical component profile (physical fitness, fat thickness, agility, muscle endurance, flexibility, power, muscle strength and balance) of the Persipura Junior Football Athletes. This study used a survey of PERSIPURA Junior Football athletes involving 39 people. The inclusions of the athletes inculde male gender, aged 21 years, height 177 cm, an ideal body weight, a healthy body, and moderate to good categories of physical fitness. The instrument used in this study were dynamometer for muscle strength; crunches for muscular endurance, push-ups, squat jumps, beam side step for agility, flexometer for flexibility, vertical jump for power, and 2.4 km running test for physical fitness. The results showed that the Persipura Junior Football athletes had a good physical fitness, less triceps fat thickness, a normal sub scapular thickness, a normal supra iliaca thickness, lack of agility, a good endurance of arm and shoulder muscles, a good endurance of abdominal muscles, an adequate flexibility, a perfect vertical jump muscle power, a good medicine ball muscle explosive power, a good full muscle strength, lack push muscle strength, and a very good balance. It concludes that to gain an optimal predominant physical component, sports science with measurable and well-programmed exercises should be applied, so that the physical component of triceps fat thickness, agility, and push muscle strength could increase. Abstrak Penelitian ini bertujuan untuk mengidentifikasi Profil Komponen Fisik Predominan (Kebugaran Jasmani, Ketebalan Lemak, Kelincahan, Daya Tahan Otot, Kelentukan, Daya Ledak Otot, Kekuatan Otot dan Keseimbangan) Atlet Pemain Sepak Bola Persipura Junior. Penelitian ini menggunakan survei terhadap atlet Sepak Bola PERSIPURA Junior sebanyak 39 orang, yang memiliki inklusi: jenis kelamin laki-laki, umur 21 tahun, tinggi badan 177 cm, berat badan ideal, berbadan sehat dan kebugaran fisik dengan kategori sedang sampai kategori baik. Instrumen untuk mengukur kekuatan otot dengan dinamometer; daya tahan otot diukur dengan sit-up, push-up, squat jumps; kelincahan diukur dengan beam side step, kelentukan diukur dengan fleksometer, daya ledak otot diukur dengan vertical jump, dan kebugaran jasmani diukur dengan tes lari 2,4 km. Hasil Penelitian menunjukkan atlet Pemain Sepak Bola Persipura Junior memiliki kebugaran jasmani baik, ketebalan lemak triceps kurang, ketebalan sub scapula normal, ketebalan supra iliaca normal, kelincahan kurang, daya tahan otot lengan dan bahu baik sekali, daya tahan otot perut baik, kelentukan cukup, daya ledak otot vertical jump sempurna, daya ledak otot medicine ball baik, kekuatan otot full baik , kekuatan otot push kurang, keseimbangan baik sekali. Agar komponen fisik predominan optimal, hendaknya menerapkan sports science dengan latihan terukur dan terprogram dengan baik sehingga komponen fisik ketebalan lemak triceps, kelincahan dan kekuatan otot push meningkat.